Pengaruh Variasi Waktu Perendaman Terhadap Daya Dukung Tanah Lempung Dan Lanau Yang Distabilisasi Menggunakan Semen - Farabi, Alward; Setyanto, Setyanto; Iswan, Iswan (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
Soil is the material that serves as a support for the construction base. Each region has different soil characteristics in other areas, there has a carrying capacity of good to bad or poor. Clay and silt soil has a bearing capacity and low soil properties. To overcome this, the need to improve the soil natures with the stabilization method. Stabilization is to improve the physical and mechanical properties of the soil so that it meets certain technical requirements. One way is with a cement stabilization. In this study, the cement used is a cement-type portland cement. This study aimed to compare the value of CBR clay and silt before and after stabilized by the addition of cement and given soaking treatment. Soil used is a type of clay taken from the village of Rawa Sragi, District Jabung, East Lampung district and silt types from  Yosomulyo Village, East Metro District, Metro City. In CBR soaking test with mixture of 9% cement with modified proctor compaction and cured for 28 days, CBR values decrease to 28,7% for clay that soaked for 28 days, while the CBR value for silt soil with the same condition descease to 37,8%. The soaking treatment is proven to decrease the value of CBR significantly compared with the optimum condition of both soil.